2004
DOI: 10.1073/pnas.0308545101
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Diels–Alder reactions catalyzed by hydrogen bonding

Abstract: Like molecules of life (e.g., proteins and DNA), many pharmaceutical drugs are also asymmetric (chiral); they are not superimposable on their mirror images. One mirror image form (enantiomer) of a drug can have desirable activity, the other not. Consequently, the development of methods for the selective synthesis of one enantiomer is of great scientific and economic importance. We report here that a simple, commercially available chiral alcohol, ␣,␣,␣ ,␣ -tetraaryl-1,3-dioxolane-4,5-dimethanol (TADDOL), cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(93 citation statements)
references
References 38 publications
3
85
1
4
Order By: Relevance
“…[42] The TADDOL catalyst 11 proved to be effective for the vinylogous Mukaiyama aldol reaction to give the corresponding aldol products highly enantioselectively (Scheme 24). The aldol products should be useful for the preparation of polyketides.…”
Section: Taddol Derivativesmentioning
confidence: 98%
“…[42] The TADDOL catalyst 11 proved to be effective for the vinylogous Mukaiyama aldol reaction to give the corresponding aldol products highly enantioselectively (Scheme 24). The aldol products should be useful for the preparation of polyketides.…”
Section: Taddol Derivativesmentioning
confidence: 98%
“…[34] These values are expected to be similar using lipase oxyanion holes, so the main concern for the viability of lipases such as CALB therefore lies in the ligandreceptor dynamics. From data on molecular catalysis reported in the literature, we can conclude that rather high catalyst concentrations are required for a reasonable activation, typically around 1-20 mol-%, [35,36,37,38] which is not possible with enzymes. Thus the binding constant between the enzyme and both substrate must be sufficiently low.…”
Section: Fig 1: (A)mentioning
confidence: 99%
“…16 After the two step transformations from the initial cycloadducts, a variety of chiral cyclohexenones were obtained with high enantioselectivies (up to 92% ee). Furthermore, our group and the Rawal group have found that the axially chiral BAMOL (1,1 biaryl 2,2 dimethanol) scaffold to be highly effective for the catalysis of the hetero Diels Alder reactions of a wide range of aliphatic and aromatic aldehydes (Scheme 7).…”
Section: Brønsted Acid Assisted Brønsted Acid Catalysts (Bbas)mentioning
confidence: 99%